Manajemen Program Jilsah Pekanan Dalam Penguatan Pendidikan Karakter Religius di Pesantren Nurul Azmi - Alinda, Deva; Setiawan, Hasrian Rudi (Universitas Labuhanbatu, 2023)
This research aims to describe the implementation of the weekly Jilsah program management, which includes planning, organizing, directing, and supervising in strengthening religious character education at Pesantren Nurul Azmi. The research uses a qualitative research method with a descriptive qualitative approach. Data collection techniques include interviews, observations, and documentation. Data analysis is carried out through data collection, data condensation, data presentation, and verification/conclusion drawing techniques. The results of the research are as follows: 1) Planning for the weekly Jilsah program has been well-executed. Mentors have implemented the program according to the schedule set by the pesantren. The first steps in planning the Jilsah weekly activities include a) determining the character to be fostered, b) developing teaching materials and methods, c) selecting mentors and their groups, and d) establishing time and location allocations; 2) Organizing the weekly Jilsah program in strengthening religious character education is carried out by detailing responsibilities, authorities, and tasks clearly. The organization creates a structured and efficient framework; 3) Directing the weekly Jilsah program in strengthening religious character involves executing the activities according to the established plan and rules; 4) Supervision of the Jilsah weekly activities in strengthening religious character is conducted with the commitment of pesantren leaders to observe, encourage, and support every aspect of the activities. Special guidance and daily religious training are provided to shape the religious character of students. There is also supervision from the Jilsah Coordinator.